2009
DOI: 10.1111/j.1759-6831.2009.00033.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of Ptychostomum (Bryaceae, Musci) inferred from sequences of nuclear ribosomal DNA internal transcribed spacer (ITS) and chloroplast rps4

Abstract: The phylogeny of Ptychostomum was first undertaken based on analysis of the internal transcribed spacer (ITS) region of the nuclear ribosomal (nr) DNA and by combining data from nrDNA ITS and chloroplast DNA rps4 sequences. Maximum parsimony, maximum likelihood, and Bayesian analyses all support the conclusion that the reinstated genus Ptychostomum is not monophyletic. Ptychostomum funkii (Schwägr.) J. R. Spence (≡Bryum funkii Schwägr.) is placed within a clade containing the type species of Bryum, B. argenteu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…9KC493853KC4939602870 m 1 Bryum argenteum MUB 40280Spain, Granada provinceN 37.07153 W 003.37355hap. 13KC493857KC493965 Bryum apiculatum Schwägr. Bryum apiculatum HBNUWang and Zhao (2009)China, Yunnan provinceEU878213FJ593892 Bryum funckii Mitt. Bryum funckii HBNUWang and Zhao (2009)China, Hunan provinceEU878209AY078332 Bryum recurvulum Schwägr. Bryum recurvulum HBNUWang and Zhao (2009)China, Hebei provinceEU878217FJ593887 Bryum yuennanense Broth. Bryum yuennanense HBNUWang and Zhao (2009)China, Yunnan provinceEU878211FJ593890…”
Section: Discussionmentioning
confidence: 99%
“…9KC493853KC4939602870 m 1 Bryum argenteum MUB 40280Spain, Granada provinceN 37.07153 W 003.37355hap. 13KC493857KC493965 Bryum apiculatum Schwägr. Bryum apiculatum HBNUWang and Zhao (2009)China, Yunnan provinceEU878213FJ593892 Bryum funckii Mitt. Bryum funckii HBNUWang and Zhao (2009)China, Hunan provinceEU878209AY078332 Bryum recurvulum Schwägr. Bryum recurvulum HBNUWang and Zhao (2009)China, Hebei provinceEU878217FJ593887 Bryum yuennanense Broth. Bryum yuennanense HBNUWang and Zhao (2009)China, Yunnan provinceEU878211FJ593890…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we use the region (1800 to 400) cm −1 for the FSD extraction of spectral features. Pohlia cruda (1), Bryum argenteum (5), and Mnium spinosum (8) are the type species of genera Pohlia, Bryum and Mnium. In order to further identify them, FSD is used to deal with the FTIR spectra of the three species.…”
Section: Fsd Analysis Of Ftir Spectralmentioning
confidence: 99%
“…The taxonomic concepts and phylogenetic relations among genera of the families Mielichhoferiaceae, Bryaceae, and Mniaceae have given rise to much controversy in recent years [4]. Studies using nuclear, plastid, and mitochondrial sequences showed that many genera of the Mielichhoferioideae and Bryaceae families are polyphyletic [5][6][7][8]. Some species of Mielichhoferiaceae, Bryaceae, and Mniaceae are difficult to distinguish by traditional phytotaxonomic methods.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations